The role of entrepreneurial cooperation - Christian Uhlig (Intereconomics, 1986)
Entrepreneurial cooperation between industrial and developing countries has gained in significance during the past decade, both in practice and in academic discussion. To what factors can this trend be attributed? What forms of cooperation are available? Where do the opportunities and risks lie?
Keywords: 330; North-South Relations